Assessment of therapy and comorbidities in patients with chronic obstructive pulmonary disease - Marković, Aleksandra; Kovačević, Milena; Ćulafić, Milica; Roganović, Maša; Jovanović, Marija; Vezmar Kovačević, Sandra; Vučićević, Katarina; Miljković, Branislava (Archives of Pharmacy, 2022)
Chronic obstructive pulmonary disease (COPD) is a highly prevalent disease characterized by progressive, irreversible airway obstruction often associated with increased inflammatory response. Symptoms including dyspnea, cough and fatigue can negatively affect patients’ quality of life. COPD is often associated with other chronic diseases that contribute to its morbidity and mortality. The aim of this research was to evaluate the therapy of COPD and comorbidities. An observational study included patients with a prescription for COPD medications. Patients’ data were collected by completing questionnaires in the community pharmacies. Descriptive analysis was performed in Microsoft® Office Excel 2010. Among 82 participants most of them were men (56.1%). Participants’ average age was 66.1±10.6 with an average disease duration of 10.2±3.8 years. Most participants (89%) used combined inhalation preparations (anticholinergic+β-agonist), anticholinergic 46.3%, salbutamol 24.4%, theophylline/aminophylline 26.9%, inhaled corticosteroid 11.0%, antibiotics 14.6% and oral corticosteroids 4.9%. Additional chronic disease was present in 97.6% of patients, with 1-5 comorbidities per patient. The majority of patients also had hypertension 73.8%, 21.3% asthma and 12.2% diabetes or heart failure. Using the mMRC (modified Medical Research Council) scale for the assessment of dyspnea, 53.7% had a score ≥2, indicating a poorly controlled disease. Almost a quarter of patients were hospitalized for exacerbation (23.2%), 53.7% were vaccinated against influenza, only 3.7% against pneumococcus and about a third were smokers (35.4%). Given the prevalence of comorbidities in this population and the complexity of therapy, counseling and monitoring by pharmacists could make a significant contribution to preventing potential drug-related problems.